Living Qur'an and Hadith in an Integrated Islamic School - Amalia, Siswi Tri; Mahariah, Mahariah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The purpose of this study focuses on the background, variety, and implementation of the Living Qur'an and Hadith program in the formation of a religious character. This research uses qualitative research with a case study approach. It was conducted at SMPIT Al-Maidani Dusun Sukun, Desa Melati II, Kec. Perbaungan. Data sources in this study refer to primary data and secondary data. Primary data were obtained from the principal, teachers of the Living Qur'an and Hadith program, and also students, while secondary data were obtained from scientific journals and books. Data collection techniques were carried out through observation, interviews, and documentation studies. While data analysis with data reduction, data presentation, conclusion drawing, and verification. The results showed that the emergence of the program was based on the interest to strengthen students' understanding of the teachings of the Qur'an and Hadith, as well as applying them in everyday life. The living Qur'an and Hadith program at SMPIT Al-Maidani has at least five kinds of activities, and they are Tahfiz, Tadarus, Tahsin, Duha prayer in congregation, and Zuhur prayer in congregation. It can be concluded that introducing religion through the practice of tadarus, tahfiz, tahsin, Duha prayer in congregation, and Zuhur prayer in congregation has a crucial role in shaping the character of students who are not secular. These activities form religious values, obedience, calmness, endurance, perseverance, regularity, spiritual awareness, and gratefulness to Allah SWT. By involving students in these activities, the school is able to create an environment that supports the development of a powerful religious character in each individual.